2016 Ieee Sensors 2016
DOI: 10.1109/icsens.2016.7808778
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasensitive magnetoelectric sensor system for the quantitative detection of liver iron

Abstract: Ultrasensitive magnetoelectric (ME) sensors have been developed using magnetostrictive/piezoelectric laminate heterostructures. This paper discusses a highly interdisciplinary design of a room temperature biomagnetic liver susceptometry system (BLS) based on the ME sensors. The ME-sensor based BLS maintains the ultrahigh sensitivity to detect the weak AC biomagnetic signals and introduces a low equivalent magnetic noise. The results reveal a “turning point” and successfully indicate the output signals to be li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…First, we performed angular measurements to determine the angle between the ME gradiometer and magnetic source. In a previous study, it was shown possible to find the distance between the magnetic source and a ME gradiometer that consisted of only two ME sensors in 2D plane [10,11]. However, it is not possible to use this pair of ME sensors to determine the angle between the magnetic source and gradiometer.…”
Section: Angular Measurement For Magnetic Source Detection In 2dmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we performed angular measurements to determine the angle between the ME gradiometer and magnetic source. In a previous study, it was shown possible to find the distance between the magnetic source and a ME gradiometer that consisted of only two ME sensors in 2D plane [10,11]. However, it is not possible to use this pair of ME sensors to determine the angle between the magnetic source and gradiometer.…”
Section: Angular Measurement For Magnetic Source Detection In 2dmentioning
confidence: 99%
“…Gradiometers are an important technology, which are widely used in magnetic field detection in open real world environments [10,11]. They allow for the rejection of common mode noises across a baseline [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the development of a room temperature BLS, exploiting the unique feature of the magnetoelectric (ME) composite sensor in detecting weak AC magnetic/electric signals in the presence of strong DC magnetic bias field. [16, 17] It should be noted that the room temperature BLS based on ME sensors is different from several other efforts of room temperature BLS which required precise cancellation of the strong bias magnetic field at the detectors location in order to pick-up very weak biomagnetic signal. [1820] Hence, the ME-sensor-based BLS technology developed is both “conventional” and “disruptive”.…”
Section: Introductionmentioning
confidence: 99%
“…As a composite sensor, the sensitivity can be enhanced by optimizing independently the piezoelectric and magnetostrictive components. In this paper, we report that, superior to PZT ceramics that we previously employed, [16, 17] the application of piezoelectric single crystal PIN-PMN-PT to the composite ME sensors enhances the ME coefficient by 10X.…”
Section: Introductionmentioning
confidence: 99%